Surrogacy in the Absence of National Legal Framework: An Analysis of Child Protection Based on Civil Law and Islamic Law in Indonesia - Solihah, Cucu; Kamilah, Anita; Yusuf, Adam Sadam Kahfi M.; Adjrun, Hasanah Subahli (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
The practice of surrogacy or surrogacy is a phenomenon of assisted reproduction that is growing globally along with advances in health technology, but has not yet received clear legal regulations in the Indonesian national legal system. The absence of this regulation creates a legal vacuum that impacts the uncertainty of the civil status and protection of children born from surrogacy practices. This study aims to analyze the implications of the surrogacy legal vacuum for child protection from the perspectives of civil and Islamic law in Indonesia. This study uses a normative legal research method with a legislative, conceptual, and comparative approach. Data were obtained through a literature review of relevant primary, secondary, and tertiary legal materials. The results show that Indonesian civil law does not provide a clear mechanism for determining the status of parents, lineage, and civil rights of children in the context of surrogacy, thus potentially ignoring the principle of the best interests of the child. Islamic law normatively does not condone the practice of surrogacy because it contradicts the principle of maintaining lineage as part of the maqashid al-shariah, but still emphasizes the obligation to protect children as a trust whose rights and dignity must be protected. An integrative analysis reveals a common ground between civil law and Islamic law in their orientation toward child protection, despite differing normative approaches. This study recommends the need to formulate a national legal policy that does not legitimize the practice of surrogacy but still guarantees comprehensive and equitable legal protection for children born.